Activation of the nicotinamide N-methyltransferase (NNMT)-1-methylnicotinamide (MNA) pathway in pulmonary hypertension. Issue 1 (December 2016) - Fedorowicz, Andrzej; Mateuszuk, Łukasz; Kopec, Grzegorz; Skórka, Tomasz; Kutryb-Zając, Barbara; Zakrzewska, Agnieszka; Walczak, Maria; Jakubowski, Andrzej; Łomnicka, Magdalena; Słomińska, Ewa; Chlopicki, Stefan
Abstract Background Pulmonary arterial hypertension (PAH) is associated with inflammatory response but it is unknown whether it is associated with alterations in NNMT activity and MNA plasma concentration. Here we examined changes in NNMT-MNA pathway in PAH in rats and humans. Methods PAH in rats was induced by a single subcutaneous injection of MCT (60 mg/kg). Changes in NNMT activity in the lungs and liver (assessed as the rate of conversion of nicotinamide (NA) to MNA), changes in plasma concentration of MNA and its metabolites (analyzed by LC/MS) were analyzed in relation to PAH progression. PAH was characterized by right ventricular hypertrophy (gross morphology), cardiac dysfunction (by MRI), lung histopathology, lung ultrastructure, and ET-1 concentration in plasma. NO-dependent and PGI2 -dependent function in isolated lungs was analyzed. In naive patients with idiopathic pulmonary hypertension (IPAH) characterized by hemodynamic and biochemical parameters MNA and its metabolites in plasma were also measured. Results MCT-injected rats developed hypertrophy and functional impairment of the right ventricle, hypertrophy of the pulmonary arteries, endothelial ultrastructural defects and a progressive increase in ET-1 plasma concentration—findings all consistent with PAH development. In isolated lung, NO-dependent regulation of hypoxic pulmonary vasoconstriction was impaired, while PGI2 production (6-keto-PGF1α ) was increased. NNMT activity increased progressively in the liver and in the lungs following MCT injection, and NNMT response was associated with an increase in MNA and 6-keto-PGF1α concentration in plasma. In IPAH patients plasma concentration of MNA was elevated as compared with healthy controls. Conclusions Progression of pulmonary hypertension is associated with the activation of the NNMT-MNA pathway in rats and humans. Given the vasoprotective activity of exogenous MNA, which was previously ascribed to PGI2 release, the activation of the endogenous NNMT-MNA pathway may play a compensatory role in PAH.